A Poetically Vision With an Imaginative Ideas By a Writer Jawaharlal Nehru: a Literary Gaolbird: Exploring the Literary Genius of Jawaharlal Nehru (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Nehru, like some great poets, had also a “negativecapability”. On the occasion of the holy festival at Vishwa Bharati in April1936, Rabindra Nath Tagore referred to Jawaharlal as the “Rituraj”,representing the season of youth and triumphant joy. Subsequently, in a letterwritten to Nehru in May 1936, he spoke of Nehru’s Autobiography as a book through which “there runs a deepcurrent of humanity which overpasses the tangles of facts and leads us to theperson who is greater than his deeds and truer than his surroundings”. It was arare tribute from one of our greatest poets and artists.